Asymptomatic portal vein aneurysms: To treat, or not to treat?. (September 2018) - Hirji, Sameer A; Robertson, Faith C; Casillas, Sergio; McPhee, James T; Gupta, Naren; Martin, Michelle C; Raffetto, Joseph D
Background: Portal vein aneurysms are rare dilations in the portal venous system, for which the etiology and pathophysiological consequences are poorly understood. Method: We reviewed the existing literature as well as present a unique anecdotal case of a patient presenting with a very large portal vein aneurysm that was successfully managed conservatively and non-operatively without anticoagulation, with close follow-up and routine surveillance. Result: The rising prevalence of abdominal imaging in clinical practice has increased rates of portal vein aneurysm detection. While asymptomatic aneurysms less than 3 cm can be clinically observed, surgical intervention may be necessary in large asymptomatic aneurysms (>3 cm) with or without thrombus, or small aneurysms with evidence of evolving mural thrombus formation on imaging. Conclusion: Portal vein aneurysms present a diagnostic challenge for any surgeon, and the goal for surgical therapy is based on repairing the portal vein aneurysm, and if portal hypertension is present decompressing via surgically constructed shunts.